2023
DOI: 10.1007/s43545-022-00603-5
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on alternative ideas on thermal phenomena of pupils with and without learning difficulties

Abstract: In the last decades, constructivism has dominated Early Childhood Science Education. Within this context, alternative ideas of pre-school pupils have been thoroughly explored and analyzed. Nevertheless, research on these ideas in individuals with learning difficulties remains scarce. Aiming to fill this gap, the present study explores alternative ideas on thermal phenomena of pupils with learning difficulties and compare them with those without learning difficulties. For this purpose, an experimental investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
2
6
0
1
Order By: Relevance
“…That is, students with special needs and particularly those with learning difficulties, can be taught thermal phenomena of melting and coagulation in mainstream classrooms and succeed in learning those phenomena as soon as appropriate teaching strategies been implemented in the teaching process. Our finding supports the literature that advocates the positive impact of inclusion in teaching and learning science to students that lie in the special needs spectrum [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…That is, students with special needs and particularly those with learning difficulties, can be taught thermal phenomena of melting and coagulation in mainstream classrooms and succeed in learning those phenomena as soon as appropriate teaching strategies been implemented in the teaching process. Our finding supports the literature that advocates the positive impact of inclusion in teaching and learning science to students that lie in the special needs spectrum [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, differences in their ideas about heat conduction were found in familiar and unfamiliar materials used by children. The same results were obtained by Katsidima et al (2023), who studied how children aged 4-9-years-old with and without learning disabilities approach the phenomenon of thermal conductivity in objects. Similar results with familiar objects are obtained by Paños et al (2021).…”
Section: Thermal Concepts and Phenomena That Are Not Directly Related...supporting
confidence: 74%
“…Discussions with the children showed that a significant number of preschool children are able to take advantage of their engagement in the different phases of the teaching-experimental process and to construct a stable precursor model for expansion and contraction., i.e., a model compatible with the model used in the school-level Science models (Βoilevin et al, 2022). In another study with children aged 4-7-years-old with and without learning disabilities, regarding the extension and contraction of metal objects, a notable percentage of the sample predicted that a metal sphere would not pass through a ring and a metal tube will be elongated after being heated, even though no mention was made of any kind of expansion (Katsidima et al, 2023).…”
Section: Thermal Concepts and Phenomena That Are Not Directly Related...mentioning
confidence: 99%
“…(Albert, 1978;Bayram et al, 2007;Kaliampos & Ravanis, 2019;Laval, 1985;Leite, 1999;Nertivich, 2018;Pathare & Pradhan, 2010;Priyadi et al, 2019;Ravanis, 2014;Rodriguez & Castro, 2014;Tin, 2018Tin, , 2019Tin, , 2022Zimmermann-Asta, 1990). Parmi ces enquêtes, très peu sont orientées vers des problèmes liés à la vie quotidienne (Fragkiadaki et al, 2021;Katsidima et al, 2023;Ravanis, 2013), et c'est précisément le problème identifié dans le débat qui l'a précédé. Cette forme d'éducation a une orientation au sein du système éducatif : acquisition de connaissances, amélioration des performances, passage d'un niveau d'enseignement à un autre.…”
Section: éDucation Et Formation : Nécessités Et Nouvelles Perspectivesunclassified